Supporting University Management System Digital Transformation with Enterprise Architecture - Hindarto, Djarot (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The present study investigates the crucial function that Enterprise Architecture performs in enabling the digital revolution of university management systems. This study investigates the incorporation of EA into education, analyzing how EA functions as a strategic underpinning to improve university processes' effectiveness, adaptability, and ingenuity. By extensively examining established models and case studies, this research examines the effects of EA on data management optimization, administrative workflow reshaping, and student experience enhancement. Through a comprehensive analysis of the interdependent connection between enterprise architecture and the digital progression of university administration, this study endeavors to furnish practical recommendations and understandings for establishments that wish to utilize EA as a catalyst for navigating the intricate challenges associated with digital transformation in the higher education sector.